2012
DOI: 10.1002/mar.20546
|View full text |Cite
|
Sign up to set email alerts
|

Product Design: Preference for Rounded versus Angular Design Elements

Abstract: Two experiments tested whether a general relative preference for objects with rounded rather than angular form (Bar & Neta, 2006, 2007) can be applied in the context of the design of consumer products. Images of product packaging—a chocolate product (Experiment 1) and water and bleach bottles (Experiment 2)—were manipulated with regard to the shape of both contour and graphics. There was a preference for rounded designs that extended to self‐report purchase likelihood—with additive effects of contour and graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(106 citation statements)
references
References 51 publications
6
95
2
3
Order By: Relevance
“…Here, one might already think of the angular bottle and label shape used on the Listerine bottle versus the rounded bottle and label used for Scope, both brands of mouthwash [75]. What is certainly clear is that there is growing interest in this area from academic researchers [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…Here, one might already think of the angular bottle and label shape used on the Listerine bottle versus the rounded bottle and label used for Scope, both brands of mouthwash [75]. What is certainly clear is that there is growing interest in this area from academic researchers [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…This holds true for lines (Bertamini, Palumbo, Gheorges, & Galatsidas, 2016; Salgado-Montejo, Tapia Leon, Elliot, Salgado, & Spence, 2015), abstract novel shapes (Bar & Neta, 2006; Bertamini et al., 2016; Silvia & Barona, 2009; Velasco et al., 2016), common objects (Bar & Neta, 2006; Westerman et al., 2012), car interiors (Leder & Carbon, 2005), and interior architectural environments (Dazkir & Read, 2012; van Oel & van den Berkhof, 2013; Vartanian et al., 2013). Even infants (Jadva, Hines, & Golombok, 2010; Quinn, Brown, & Streppa, 1997) and great apes (Munar, Gómez-Puerto, Call, & Nadal, 2015) demonstrate this preference.…”
Section: The Robustness Of Curvature Preferencesmentioning
confidence: 99%
“…Of course, given our general preference for curvature over angularity (e.g., Westerman, Gardner, Sutherland, White, Jordan, Watts, & Wells, 2012 [67]; see Gómez-Puerto, Munar, & Nadal, 2016 [68], for a recent historical overview), it could be suggested that opting for a rounder form for one's glassware ought, generally-speaking, to be preferred (over straight-sided glassware). However, that said, if a 4 This does, though, raise the question of whether any of the differences in drinking behaviour might not be attributable, at least in part, to any differences in the multisensory tasting experience that result from the change in the form/shape of the glassware.…”
Section: Crossmodal Correspondences Between Shape Properties and Tastmentioning
confidence: 99%